The Effectiveness of Lego Therapy on the Social Skills of Preschool Children with Hearing Loss - Mohammad Ashori; Mahdieh Safari (Vesnu Publications, 2019)
Introduction: Lego therapy is one of the interventional programs shown to encourage significant improvement in the social skills of children with hearing loss. The purpose of this study was to investigate of the effectiveness of Lego therapy on the social skills of preschool children with hearing loss in Isfahan City, Iran. Materials and Methods: The present research was a semi-experimental study with pretest/posttest design and control group. The participants were 24 preschool children with hearing loss aged 4-6 years. Subjects were selected using convenient sampling method from Ava mother child rehabilitation center. They were divided into experimental and control groups (n = 12). The experimental group received Lego therapy program in 8 sessions (45 minutes per session), while control group did not participated in this type program. Data gathering tool was Matson Social Skills Questionnaire. Data were collected before and after the training sessions, and were analyzed using multivariate analysis of covariance (MANCOVA). Results: Lego therapy had a significant effect on social skills and all subscales (appropriate social behavior, asocial behavior, aggressive and impulsive behavior, superiority and self-confidence, and communication with peers) in the experimental group (P < 0.001). Conclusion: Lego therapy improved the social skills of preschool children with hearing loss. In fact, Lego therapy uses play to develop social skills via creating opportunities to make relationships with others.